Newly developed EMF cell with zirconia solid electrolyte for measurement of low oxygen potentials in liquid Cu-Cr and Cu-Zr alloys - Katayama I.; Tanigawa S.; Živković D.; Hattori Y.; Yamashita H. (Journal of Mining and Metallurgy. Section B: Metallurgy)
In order to measure the very low oxygen potential by use of stabilized zirconia solid electrolyte emf method, a new cell construction was devised. The idea was based on Janke but a zirconia rod was used instead of the zirconia crucible which contacts liquid alloy electrode. The cell was used for determination of the oxygen potentials in liquid dilute Cu-Cr and Cu-Zr alloys. The reference electrode was Cr,Cr2O3. Emf measurements were performed in the temperature range of 1400-1580K and composition range of 0.198-3.10at%Cr-Cu alloys, and 1380-1465K, 0.085-0.761at%Zr-Cu alloys. The composition of liquid alloys were determined by picking up from the liquid alloys and ICP analysis. By use of the newly devised cell construction in this study, stable emf values were obtained at each temperature and alloy composition. Emf values were corrected by using the parameter for electronic contribution of the YSZ. Activity of Cr obeys Henry’s law and activity coefficient at infinitely dilute alloys of Cr in Cu-Cr alloys are: lng0 Cr =(3.80 at 1423K), (3.57 at 1473K), (3.38 at 1523K) and (3.20 at 1573K). At 1423 K activity coefficient of Zr at infinitely diluted alloy is lnγo Zr = -4.0.